Comparison of structural occipital and iliac bone grafts for instrumented atlantoaxial fusions in pediatric patients: Radiologic research and clinical outcomes - Liang, Zhi-Hui; Zhang, Yue-Hui; Liu, Hai-Tao; Zhang, Qiu-Qi; Song, Jia; Shao, Jiang (Frontiers in Surgery, 2023)
Background: Structural autografts harvested from the iliac bone have been used in atlantoaxial fusion; they have been the gold standard for years. However, emerging occipital bone grafts have the advantage of avoiding donor-site morbidity and complications. Thus, we compared the clinical outcomes of structural autografts from the occipital bone or iliac crest and discussed the clinical significance of occipital bone grafts in pediatric patients. Methods: Pediatric patients who underwent posterior fusion using occipital bone grafts (OBG) or iliac bone grafts (IBG) between 2017 and 2021 were included in this study. Data on clinical outcomes, including operation time, estimated blood loss, length of hospitalization, complications, fusion rate, and fusion time, were collected and analyzed. Additionally, 300 pediatric patients who underwent cranial computed tomography scans were included in the bone thickness evaluation procedure. The central and edge thicknesses of the harvested areas were recorded and analyzed. Results: Thirty-nine patients were included in this study. There were no significant differences in patient characteristics between the OBG and IBG groups. Patients in both groups achieved a 100% fusion rate; however, the fusion time in the OBG group was significantly longer than that in the IBG group. Estimated blood loss, operation time, and length of hospitalization were significantly lower in the OBG group than those in the IBG group. The surgery-related complication rate was lower, but not significantly, in the OBG group than that in the IBG group. For occipital bone thickness evaluation, a significant difference was found between the young and old groups, with no significant sex differences. Conclusion: The use of OBG for atlantoaxial fusion is acceptable for pediatric patients with atlantoaxial dislocation, avoiding donor-site morbidity and complications.